Interleukin 25 and its biological features and function in intestinal diseases - Wei Jiang; Zehui Wang; Jun Zhang; Minghui Li (Central European Journal of Immunology, 2023)
Interleukin 25 (IL-25), also known as IL-17E, is a member of the IL-17 cytokine family and an important regulator of the type 2 immune response. Accumulating evidence suggests that IL-25 interacts with diverse immune as well as non-immune cells and plays a rather complicated role in different backgrounds of multiple organs. IL-25 has been studied in the physiology and pathology of the intestine to some extent. With epithelial cells being an important source in the intestine, IL-25 plays a key role in intestinal immune responses and is associated with inappropriate allergic reactions, autoimmune diseases, and cancer tumorigenesis. In this review, we discuss the emerging comprehension of the biology of IL-25, as well as its cellular sources, targets, and signaling transduction. In particular, we discuss how IL-25 participates in the development of intestinal diseases including helminth infection, inflammatory bowel diseases, food allergy and colorectal cancer, as well as its underlying role in future therapy.